A Sound Interpretation of Leśniewski's Epsilon in Modal Logic KTB - Takao Inoue (Bulletin of the Section of Logic, 2022)
In this paper, we shall show that the following translation \(I^M\) from the propositional fragment \(\bf L_1\) of Leśniewski's ontology to modal logic \(\bf KTB\) is sound: for any formula \(φ\) and \(ψ\) of \(\bf L_1\), it is defined as